The impact of interest rates on the inflation rate in the Iraqi economy for the period (2004-2024) - Faraj, Assistant Professor: sikna; Imam , Assistant Professor : Risan (The Gulf Economist, 2025)
The interest rate is an effective monetary policy tool that plays a significant role in influencing economic activity and is an important indicator that affects inflation rates in particular. Using data for the period (2004-2024), the researcher used econometric analysis to determine the impact of the interest rate and predict the nature of the relationship in the future through cointegration. This was based on a set of tests, including stability tests, for both the interest rate and the inflation rate. It was found that the relationship between the interest rate and the inflation rate is an inverse relationship, and that there is cointegration between the variables. The study relied on simple regression analysis to demonstrate the impact of the interest rate on Iraqi economic activity through inflation during the study period. The researcher reached a set of conclusions and recommendations, the most important of which are: the existence of a long-term balance between the interest rate and inflation, which means that the interest rate is capable of correcting deviations and structural imbalances in the Iraqi economy in the long term. The researcher concluded that the interest rate is ineffective in the Iraqi economy in the short term, because the relationship between the interest rate and the inflation rate in the short term is a direct and statistically significant relationship. However, in the long term, the relationship is insignificant, as the economy suffers from structural imbalances.